NBAS mutations cause a multisystem disorder involving bone, connective tissue, liver, immune system, and retina. (19th August 2015) - Segarra, Nuria Garcia; Ballhausen, Diana; Crawford, Heather; Perreau, Matthieu; Campos‐Xavier, Belinda; van Spaendonck‐Zwarts, Karin; Vermeer, Cees; Russo, Michel; Zambelli, Pierre‐Yves; Stevenson, Brian; Royer‐Bertrand, Beryl; Rivolta, Carlo; et al.
Abstract : We report two unrelated patients with a multisystem disease involving liver, eye, immune system, connective tissue, and bone, caused by biallelic mutations in the neuroblastoma amplified sequence ( NBAS ) gene. Both presented as infants with recurrent episodes triggered by fever with vomiting, dehydration, and elevated transaminases. They had frequent infections, hypogammaglobulinemia, reduced natural killer cells, and the Pelger–Huët anomaly of their granulocytes. Their facial features were similar with a pointed chin and proptosis; loose skin and reduced subcutaneous fat gave them a progeroid appearance. Skeletal features included short stature, slender bones, epiphyseal dysplasia with multiple phalangeal pseudo‐epiphyses, and small C1‐C2 vertebrae causing cervical instability and myelopathy. Retinal dystrophy and optic atrophy were present in one patient. NBAS is a component of the synthaxin‐18 complex and is involved in nonsense‐mediated mRNA decay control. Putative loss‐of‐function mutations in NBAS are already known to cause disease in humans. A specific founder mutation has been associated with short stature, optic nerve atrophy and Pelger–Huët anomaly of granulocytes (SOPH) in the Siberian Yakut population. A more recent report associates NBAS mutations with recurrent acute liver failure in infancy in a group of patients of European descent. Our observations indicate that the phenotypic spectrum of NBAS deficiency is wider than previously known and includes skeletal, hepatic, metabolic, and immunologic aspects. Early recognition of the skeletal phenotype is important for preventive management of cervical instability. © 2015 Wiley Periodicals, Inc.